Awake versus intubated video-assisted thoracoscopic surgery for pleural disease: a retrospective cohort study from a single tertiary center - Saglam, Omer Faruk; Kilic, Burcu; Ekinci Fidan, Merve; Sayilgan, Nevzat Cem; Kara, H. Volkan; Turna, Akif; Kaynak, Kamil; Ersen, Ezel (Frontiers in Surgery, 2025)
IntroductionAwake video-assisted thoracoscopic surgery (A-VATS) has gained increasing attention as an alternative to classical intubated VATS (I-VATS), particularly in patients with comorbidities that have increased the risk of surgery under general anesthesia. This study aimed to compare the perioperative and postoperative outcomes of patients who underwent A-VATS vs. I-VATS for pleural diseases.MethodsThis is a retrospective cohort study including patients who underwent A-VATS (n = 22) and I-VATS (n = 37) for pleural diseases between July 2015 and March 2023 at a single tertiary step medical center. Patients considered unsuitable or at high risk for I-VATS due to anesthetic risk or comorbidities were allocated to the A-VATS group. Demographic characteristics, comorbidities, risk scores, spirometry results, surgical outcomes, anesthesia satisfaction, surgical and other complications, and laboratory parameters were analyzed.ResultsA-VATS had significantly lower NRS scores at all postoperative timepoints (1, 12, 48 h; p < 0.01) and reduced NSAID use (p = 0.04), whereas opioid use was similar between the groups. The incidence of postoperative atelectasis was higher in the I-VATS group (p < 0.001). Earlier oral intake, mobilization, and return of bowel function were observed in the A-VATS group (all values compared were p < 0.001). Although the hospital stay was longer in the A-VATS group (5.0 vs. 2.0 days; p = 0.01), there was no difference in hospitalization costs between the groups (p > 0.05). There was no difference in the overall complication rates (p > 0.05). Hematological and biochemical parameter changes were similar between the groups.ConclusionsA-VATS is a potential feasible alternative in appropriate patients who have a higher risk with I-VATS. A-VATS offers favorable outcomes in terms of postoperative pain control and better recovery so may replace I-VATS. However, its use requires careful patient selection and perioperative planning due to the occurrence of severe complications in some cases. Prospective randomized, patient matched larger and multiple study groups are needed and in our future plan to confirm these findings and optimize the perioperative and postoperative protocols for A-VATS.